Dehesa ecosystem: Production and preservation (Options Méditerranéennes, 1999)
The Dehesa is an ecosystem in which species of herbs, bushes and trees coexist in a semi-desert regime, contributingto the feeding of domestic and wild animals. The improvement and exploitation of these agrosylvopastoral systems must be founded on the principles of preseofr vthaetio ne nvironment and the idea of creating systems that can be maintained with a correct usage of natural resources. Fertilization of the natural pastures, the introduction of new pasture species and varieties, the favouring of the species of bush that have a forage value and the preservationo f the arboreous stratum are methods which will alluosw t o preserve this ecosystem